Ideal Teacher Qualities as Perceived by High-Ability Students from Low Socio-Economic Backgrounds: A Study based in West Bengal - Roy, Paromita; Dasgupta, Surabhi (INDIAN EDUCATIONAL REVIEW, 2017)
This study was aimed at understanding perceptions of underprivileged high-ability middle school students regarding the qualities they considered ‘best’ in their favourite science teachers. Almost 74 students identified from a cohort of 733 Class VIII students from five rural schools in the state of West Bengal (India) rated their best science teacher by indicating certain qualities and attributes which were enlisted in a questionnaire. Results indicate that for the concerned group of students it is far more crucial that a good teacher values their problems and is patient and understanding rather than the fact that he or she is a domain expert. Good guidance and infusion of the spirit of independent thinking in a student are also sought after virtues but on the whole it is the humane qualities which stand out because of perhaps the socio-economic background of the students concerned.